Implementation of Evaluation Tool Development Using the Quizizz Application in Islamic Education Learning in Class 8 of SMP Plus Pondok Modern Al-Aqsa - Basyari*, Zen Anwar Saeful; Nugraha, Mulyawan Safwandy (Riwayat: Educational Journal of History and Humanities, 2023)
The evaluation of learning that has been running and carried out in many schools uses written or oral evaluation, it makes students feel monotonous with the evaluation system. In the development of evaluation, several tools can be used in the evaluation, one of which is the Quis system where the tool uses the Quizizz program. This article aims to analyze the application of evaluation instruments in the context of learning Islamic Religious Education (PAI) through the use of the Quizizz application. Are there changes to students that can be used as motivation for students in the evaluation process or does even using this instrument make students or the evaluation system not work well? This research adopts a qualitative approach with field research methods, where data is obtained and the research process is carried out in specific locations. The study was conducted in the 8th grade of SMP Plus Al Aqsa. The results showed that the use of Quizizz in PAI learning in the classroom was effective, able to motivate students, and resulted in improvements in their exam performance.